A Chiral Macrocyclic Oligothiophene with Broken Conjugation – Rapid Racemization through Internal Rotation. Issue 1 (28th December 2018) - Weiland, Kevin J.; Münch, Nathalia; Gschwind, Wanja; Häussinger, Daniel; Mayor, Marcel
Abstract: A macrocyclic oligothiophene with an integrated pseudo ‐ para substituted [2.2]paracyclophane has been achieved. The synthetic sequence relies on alternating steps of halogenation‐ and Suzuki ‐coupling conditions. By employing a modified Eglinton reaction under high dilution conditions, the macrocycle is closed and the obtained diacetylene is efficiently transferred to the corresponding thiophene. The molecule is fully characterized and its dynamic racemization is analyzed by variable temperature NMR experiments. The racemization barrier hints with 38 kJ/mol at rapid enantiomerization at room temperature by Mislow 's ' Euclidian rubber glove' enantiomerization process. Macrocycle formation results in red‐shifted absorption and emission spectra, hinting at increased conjugation through the oligothiophene versus the trough space conjugation through the [2.2]paracyclophane. Abstract :